Consumer Information Search for Credence Goods and the Use of Consumer Generated Content - M'hamdi, Hasnae (2012)
Consumer information search is a vital stage in the decision making model and it is the most time consuming phase. This study attempts to investigate consumer information search behavior especially for credence goods and the use of consumer generated content (CGC). The internet enabled customers with a great deal of shared knowledge and information online. Moreover, when customers are searching information about credence goods, they often rely on CGC. There is an emerging interest on the effectiveness of CGC because it provides insights into consumer behavior and enables companies with new opportunities for communicating with customers. Therefore, this research study adopts a general view of CGC and discusses social media in particular as the main source that consumers opt for while searching for product related information.